THE INFLUENCE OF ISLAMIC LIFESTYLE, HALAL CERTIFICATION, AND SOCIAL MEDIA EXPOSURE ON PURCHASING DECISIONS AT MIXUE OUTLETS IN SERANG CITY - Imanuddin, Febri; Ahyakudin, Ahyakudin; Pardiansyah, Elif; Ginanjar, Rah Adi Fahmi (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to examine the influence of Islamic lifestyle, halal certification, and social media exposure on purchasing decisions at Mixue outlets in Serang City. Design/Methodology/Approach: The research used a quantitative approach with survey data collected from 190 respondents. Multiple linear regression analysis was applied using SPSS 26. Prior to hypothesis testing, classical assumption tests including normality, multicollinearity, and heteroscedasticity were conducted to ensure data validity. Research findings: The results showed that Islamic lifestyle, halal certification, and social media exposure each had a positive and significant effect on purchasing decisions. The coefficient of determination (R²) was 0.503, indicating that 50.3% of the variation in purchasing decisions could be explained by the three independent variables. The remaining 49.7% was influenced by other factors outside the model. Theoretical Contribution/Originality: This research contributes to the understanding of consumer behavior in the context of halal and Islamic marketing, especially within the growing market segment of Muslim consumers in non-traditional halal industries such as ice cream chains. It highlights the integration of religious values and digital influence in shaping consumer preferences. Practitioners/Policy Implications: The findings suggest that food and beverage companies targeting Muslim consumers should not only focus on halal certification but also promote Islamic lifestyle compatibility and engage actively on social media platforms to enhance purchasing behavior. These insights are valuable for marketing strategists and brand managers operating in multicultural environments. Research Limitations/Implications: The study is limited to Mixue outlets in Serang City, which may not fully represent broader consumer behavior across different regions. Future research should involve comparative studies across cities or include moderating variables such as income or education level for more nuanced insights.